Assessing competencies for social and emotional learning : conceptualization, development, and applications - Burrus, Jeremy; Rikoon, Samuel H.; Brenneman, Meghan W. (New York, NY : Routledge, 2022)
"Assessing Competencies for Social and Emotional Learning explores the conceptualization, development, and application of assessments of competencies and contextual factors related to social and emotional learning (SEL). As programs designed to teach students social and emotional competencies are being adopted at an ever-increasing rate, new measurements are needed to understand their impact on student attitudes, behaviors, and academic performance. This book integrates standards of fairness, reliability, and validity, and lessons learned from personality and attitude assessment to facilitate the principled development and use of SEL assessments. Education professionals, assessment developers, and researchers will be better prepared to systematically develop and evaluate measures of social and emotional competencies"--
Introducing assessing competencies for social and emotional learning : conceptualization, development, and applications / Jeremy Burrus, Meghan W. Brenneman, and Samuel H. Rikoon -- An integrative perspective on SEL frameworks / Alex Casillas, Brent Roberts, and Stephanie Jones -- A developmental framework for SEL assessment : context, culture, and equity / Rebecca J. Bulotsky-Shearer, Pilar Alamos, Jenna Futterer, and Jhonelle Bailey -- Developing a validity argument for social and emotional learning assessments : consideration of uses and evidence / Krista Mattern and Kate Walton -- Standards for SEL assessment / Michael C. Rodriguez -- Principled and practical approaches to developing SEL assessments / James C. DiPerna, Pui-Wa Lei, Christopher J. Anthony, and Stephen N. Elliott -- Self-report and observer ratings : item types, measurement challenges, and techniques of scoring / Ricardo Primi, Nelson Hauck-Filho, and Felipe Valentini -- Novel technology-based SEL assessments / Nicole M. Russo-Ponsaran, Ashley Karls, and Clark McKown -- When actions speak louder than words : stealth assessment of social and emotional skills / Kristin Stoeffler, Yigal Rosen, and Jason Way -- Connecting measurement and action : reporting results in the SEL context / April L. Zenisky -- Assessment of social and emotional learning for admissions and selection / Phoebe Hessen, Samuel D Lee, and Nathan R. Kuncel -- Multi-informant formative and summative assessments of SEL skill development / Stephen N. Elliott, Christopher J. Anthony, Pui-Wa Lei, and James C. DiPerna -- School climate assessments : measuring the conditions that support students' social and emotional competencies / Juliette Berg, Anne Diffenderffer, and David Osher -- Social and emotional learning (SEL) skills cannot thrive on shaky foundations : preventing and detecting mental health problems in school-based programs / Suniya S. Luthar and Nicole Zillmer -- SEL assessment : building a rigorous foundation in support of an innovative, equitable future / Samuel H. Rikoon, Meghan W. Brenneman, and Jeremy Burrus.
Keywords: Affective education; Affective education -- Evaluation; Educational evaluation; School children -- Mental health; School environment; EDUCATION / Testing & Measurement; EDUCATION / Educational Psychology